Territorial hunting management: problems of strategic planning and law regulation - I. A. Grebnev (Аграрная наука Евро-Северо-Востока, 2022)
The article analyzes the problems of territorial hunting management in the Russian Federation. The subjects of the analysis were regulations of federal legal acts controlling the organization and conduct of strategic planning in the Russian Federation, the organization and conduct of territorial hunting management, as well as 60 approved and publicly available schemes for the placement, use and protection of hunting resources on the territory of the subject of the Russian Federation. During the study there were used general scientific research methods, as well as formal-legal, comparative-legal, technical-legal research methods and the method of legal modeling. It is shown that there are a number of systemic problems of state management of the hunting sphere and the storage of hunting resources that negatively affect the regional strategic planning of hunting nature management. Examples of typical and reproducible in different variations in the regions defects of regional hunting planning are given. A set of measures to improve the organizational and legal mechanism of territorial hunting management is proposed: firstly, the author substantiates the need to compile such documents only within the framework of scientific research; secondly, the expediency of fixing the regulations on the presence of elements of adaptive management in the documents of territorial hunting management at the federal level is shown; thirdly, the need for mandatory public and professional discussion of the draft document of territorial hunting management at the stage of acceptance of work is indicated; fourthly, it is recommended to increase the level of involvement of hunters, hunting users and other interested parties in the field of hunting nature management into the process of approving and implementing sectoral development plans, including by granting full powers to state authorities of the subjects of the Russian Federation in the formation of a regional component of hunting agreements.